Exploring social change : America and the world - Harper, Charles L.; Leicht, Kevin T. (London : Routledge, 2019)
Exploring Social Change provides a compelling analysis of theories that explain social change, innovation, social movements, and revolution, and concludes with reflections about how individuals do and should live in an uncertain and rapidly changing world. Written in a personal and clear manner, the authors provide definitions of key terms and analysis of theories and ideas from the study of social change. The seventh edition includes updated examples reflecting the social changes that have occurred in the world around us, including new discussions on the environmental and social landscapes, as well as updated methods and discussions that reflect that changing field of social change study
Includes bibliographical references and index.
Keywords: Social change; Social change -- United States